Optimalisasi produktivitas pengupasan biji kopi melalui modifikasi mesin pengupas - Muttaqin, Ahmad Nurul; Mihdar, Uswatul Hasanah (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
The aim of this research is to modify the coffee bean husking machine to enhance the quality and efficiency of the husking process. The modifications include the addition of a spring mechanism in the grinding space, enabling the outer roller to move flexibly in accordance with the size of the entering coffee beans. Furthermore, these changes also consider reducing the percentage of broken coffee beans during the husking process. The machine underwent two rounds of testing, with three samples tested under two different drying conditions. The research results demonstrate the success of the modifications in achieving their objectives. The machine's capability to husk coffee beans up to the parchment layer, not just the husk, indicates an improvement in the quality of the husking process. The quantity of successfully husked coffee beans also increased, while the percentage of broken beans decreased. By enhancing the quality and quantity of coffee beans produced by this machine, the modifications can significantly benefit coffee farmers. Additionally, this study utilized Autodesk Fusion 360 software to enable virtual assembly of machine components before physical production. The outcomes of the virtual assembly aided in understanding the machine's functionality and the interactions among its components. Therefore, the modifications to the coffee bean husking machine have assisted coffee farmers in producing higher-quality beans and expediting the coffee processing process.